Penerapan Metode Topsis Untuk Menentukan Ustadz Dan Ustadzah Penerima Bonus Di Pesantren - Antonius Arie; Wahyu Hidayat (Universitas Binaniaga Indonesia, 2023)
In teaching and learning activities at Islamic boarding schools, the role of ustadz and ustadzah as teaching staff has a major influence on the quality of graduation of students and female students. The appreciation of the pesantren is by giving awards in the form of financial bonuses according to their performance. We need a Decision Support System to solve this problem. The TOPSIS method can help the decision-making calculation process for many alternatives and criteria that can produce rankings by calculating the distance between the best and worst solutions. In this study the TOPSIS method was carried out using 15 alternatives and 5 criteria and importance weights that had been determined by the pesantren, namely 20% craft, 20% activity, 30% expertise, 15% education and 15% working period. The final result of the TOPSIS calculation found that Alternative 12 got the highest score of 0.5831 and Alternative 13 got the lowest score of 0.2850.